VEGETATIVE PERFORMANCE OF MAIZE (Zea Mays L) ON DEGRADED SOIL AS AFFECTED BY COMPOSTED ORGANIC RESIDUES - OLOWOAKE, A. A.; ADEOYE , G. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The evaluation of five different compost types; Poultry manure + Mucuna husk (PmMh), Poultry manure + Leaf litter (PrnLl), Pou1ti-y manure +Rice straw (PmRs), Podt~ -f Leaf litter + Rice straw (PmLlRs) and Poultry manure + Leaf litter + Mucuna husk (PrnLlMh) on the performance of maize under greenhouse conditions was investigated. Maize variety ACR 9931-DMRSR treated with 1.5, 3.5, 4.5 and 6.0 t ha-1 each of the compost treatments was used in first cropping, while NPK 15-15-15 applied at 300, 400 and 600 kg ha-1 and control (no fertilizer) were also observed in the second cropping. A completely randomized experimental design with 24 treatments in three replications was conducted. Significant differences (p< 0.05) were found in plant height and dry matter yield of maize. N, P and K uptake of maize from 1.5 t ha-1 PmLlMh were 20.4, 6.2, 21.9 mg-1 pot respectively and these values were significantly (p< 0.05) higher than that of uptake values obtained from NPK treatment. Residual effect of plant height, dry matter yield and nutrient uptake of maize values obtained from 1.5 t/ha PmLlMh was also significantly (p< 0.05) higher than that of NPK values. It was concluded that PmLlMh at 1.5 t /ha-l could serve as effective compost for maize production.